Surgical outcomes related to invasive EEG monitoring with subdural grids or depth electrodes in adults: A systematic review and meta-analysis. (August 2019) - Toth, Marton; Papp, Kata Szilvia; Gede, Noemi; Farkas, Kornelia; Kovacs, Sandor; Isnard, Jean; Hagiwara, Koichi; Gyimesi, Csilla; Kuperczko, Diana; Doczi, Tamas; Janszky, Jozsef
Highlights: This meta-analysis focus on surgical outcomes originating from SDG- or SEEG-monitors. In SDG-group, ratio of seizure-free outcomes reached 55.9%, while in SEEG-group, it was 64.7%. In lesional cases, Engel I outcome was 57.3% in SDG-group, while in SEEG-group, it was 71.6%. In the temporal cases, seizure-freedom achieved 56.7% in SDG-group, in SEEG-group it was 73.9%. SEEG-monitors were associated non-inferiorly with seizure-freedom compared to SDG-monitors. Abstract: Purpose: Resective epilepsy surgery based on an invasive EEG-monitors performed with subdural grids (SDG) or depth electrodes (stereo-electroencephalography, SEEG) is considered to be the best option towards achieving seizure-free state in drug-resistant epilepsy. The authors present a meta-analysis, due to the lack of such a study focusing on surgical outcomes originating from SDG- or SEEG-monitors. Method: English-language studies published until May 2018, highlighting surgical outcomes were reviewed. Outcome measures including total number of SDG- or SEEG-monitors and resective surgeries; consecutively followed surgical cases; surgical outcomes classified by Engel in overall, temporal/extratemporal and lesional/nonlesional subgroups were analyzed. Results: 19 articles containing 1025 SDG-interventions and 16 publications comprising 974 SEEG-monitors were researched. The rate of resective surgery deriving from SDG-monitoring hovered at 88.8% (95%CI:83.3–92.6%) (I 2  = 77.0%;p < 0.001); in SEEG-group, 79.0% (95%CI:70.4–85.7%) (I 2  = 72.5%;p < 0.001) was measured. After SDG-interventions, percentage of post-resective follow-up escalated to 96.0% (95%CI:92.0–98.1%) (I 2  = 49.1%;p = 0.010), and in SEEG-group, it reached 94.9% (95%CI:89.3–97.6%) (I 2  = 80.2%;p < 0.001). In SDG-group, ratio of seizure-free outcomes reached 55.9% (95%CI:50.9–60.8%) (I 2  = 54.47%;p = 0.002). Using SEEG-monitor, seizure-freedom occurred in 64.7% (95%CI:59.2–69.8%) (I 2  = 11.9%;p = 0.32). Assessing lesional cases, likelihood of Engel I outcome was found in 57.3% (95%CI:48.7%–65.6%) (I 2  = 69.9%;p < 0.001), using SDG; while in SEEG-group, it was 71.6% (95%CI:61.6%–79.9%) (I 2  = 24.5%;p = 0.225). In temporal subgroup, ratio of seizure-freedom was found to be 56.7% (95%CI:51.5%–61.9%) (I 2  = 3.2%;p = 0.412) in SDG-group; whereas, SEEG-group reached 73.9% (95%CI:64.4%–81.6%); (I 2  = 0.00%;p = 0.45). Significant differences between seizure-free outcomes were found in overall (p = 0.02), lesional (p = 0.031), and also, temporal (p = 0.002) comparisons. Conclusions: SEEG-interventions were associated, at least, non-inferiorly, with seizure-freedom compared with SDG-monitors in temporal, lesional and overall subgroups.